Assessment of Patient Satisfaction and Acceptance of Acupuncture as an Alternative Therapy in Dental Practice - Tapas K. Sarkar; Divya Pandya; Mohit Sharma; Sandip Kulavi; Priyanka Dausage; Anwesha Banerjee (Journal of Pharmacy and Bioallied Sciences)
Objective: To evaluate patient satisfaction and acceptance of acupuncture in dental practice. Methods: This randomized controlled study involved 30 participants (15 males, 15 females, mean age 38.2 years) requiring mandibular third molar extraction. Patients were randomly assigned to receive either real or placebo acupuncture. Pain intensity was assessed using a 4-point scale, and patients’ acceptance of and satisfaction with acupuncture were measured. The study was conducted at an oral and maxillofacial surgery clinic. Results: Toothache was the most common dental issue (16.7%). Participants showed moderate to high levels of acceptance toward acupuncture (mean score of 3.37 on a 4-point scale) and satisfaction with the treatment (mean score of 3.50). Conclusion: The study demonstrates a positive reception of acupuncture in dental settings, with moderate to high levels of patient acceptance and satisfaction. These findings suggest that acupuncture could be a valuable adjunctive therapy in comprehensive dental care, particularly for pain management and anxiety reduction. However, further research is needed to fully establish its efficacy across various dental procedures.